2021
DOI: 10.1002/adom.202100461
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Nondoped Organic Light‐Emitting Diode Based on a Thermally Activated Delayed Fluorescence Emitter with 1D Intermolecular Hydrogen Bonding Interactions

Abstract: Research data are not shared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Our previous studies demonstrated that inside films that contain PXZ and Py/Pm series intermolecular hydrogen bonding is facilely formed, which is beneficial to improve the performances of non-doped OLEDs. 28,29 Herein, we used two novel A segments, namely 2,6-di(pyridin-3-yl)pyrimidine (PyPm) and 2-(pyridin-3-yl)-4,5′-bipyrimidine (PmPm) that have stronger electron-withdrawing abilities than previously employed A segments, namely TPy and DPmP; while the D segments are still PXZ to realize non-doped orange-red systems. The only difference of PyPm and PmPm is the peri -azaaromatic ring (the substituent labeled number 6 in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous studies demonstrated that inside films that contain PXZ and Py/Pm series intermolecular hydrogen bonding is facilely formed, which is beneficial to improve the performances of non-doped OLEDs. 28,29 Herein, we used two novel A segments, namely 2,6-di(pyridin-3-yl)pyrimidine (PyPm) and 2-(pyridin-3-yl)-4,5′-bipyrimidine (PmPm) that have stronger electron-withdrawing abilities than previously employed A segments, namely TPy and DPmP; while the D segments are still PXZ to realize non-doped orange-red systems. The only difference of PyPm and PmPm is the peri -azaaromatic ring (the substituent labeled number 6 in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we have proposed a new molecular design concept by using suitable intermolecular hydrogen bonding to modulate molecular packing to develop high-performance non-doped OLEDs. 28,29 Suitable intermolecular hydrogen bonding interactions favor forming supramolecular frameworks, which can not only strictly suppress the exciton quenching via suppressing intermolecular close π–π stacking, but also help to increase the rigidity of the supramolecular framework and thus relieve non-radiative decays. In this study, with an aim to develop high-performance orange-red non-doped OLEDs with intermolecular hydrogen bonds, we used phenoxazine (PXZ) as the D segment, and joint pyridine (Py)/pyrimidine (Pm) series as the A segments and constructed two novel TADF emitters 10-(4-(2,6-di(pyridin-3-yl)pyrimidin-4-yl)phenyl)-10 H -phenoxazine (PyPmP) and 10-(4-(2-(pyridin-3-yl)-[4,5′-bipyrimidin]-6-yl)phenyl)-10 H -phenoxazine (PmPmP) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…By replacing the peripheral pyridine ring in 119 with a more electron-withdrawing pyrimidine unit, we further synthesized a novel TADF emitter 121 . 111 Unlike the formation of a 3D framework in 119 , the X-ray data show that a 1D chain can be observed in 121 . Such a linear chain structure can effectively keep the electron-rich PXZ cores in neighboring molecules apart from each other such that triplet-related exciton quenching can be well suppressed.…”
Section: Tadf Emitters For Nondoped Oledsmentioning
confidence: 86%
“…The nondoped OLED based on the mTPy-PXZ with such suitable intermolecular H-bonds exhibits the state-of-the-art performance with maximum EQE of up to 23.6% with only 7.2% roll-off at 1,000 cd m −2 . Recently, they designed a new TADF emitter, DPmP-PXZ (Figure 1G), composed of 2,6-di (pyrimidin-5-yl) pyridine (DPmP) as electron-acceptor and phenoxazine (PXZ) as electron-donor (Shi et al, 2021). Further intermolecular hydrogen bonding between the DPmP and PXZ groups favors the formation of extended linear chains of molecules instead of 3D frameworks (Figure 2D).…”
Section: H-bond Interactions In Organic Green Emittersmentioning
confidence: 99%